HER‐2/neu gene amplification in relation to expression of HER2 and HER3 proteins in patients with esophageal adenocarcinoma. Issue 3 (21st October 2013) - Yoon, Harry H.; Sukov, William R.; Shi, Qian; Sattler, Christopher A.; Wiktor, Anne E.; Diasio, Robert B.; Wu, Tsung‐Teh; Jenkins, Robert B.; Sinicrope, Frank A.
Abstract : BACKGROUND: Human epidermal growth factor receptor 2 (HER2) is a therapeutic target in patients with esophageal adenocarcinoma (EAC), with gene amplification used as a selection criterion for treatment, although to the authors' knowledge the concordance between amplification and HER2 protein expression remains undefined in EAC. Furthermore, the association between HER2 and its interacting partner, human epidermal growth factor receptor 3 (HER3), is unknown yet appears to be of potential therapeutic relevance. METHODS: Patients with untreated EACs (N = 673) were analyzed for HER2 amplification and polysomy 17 by fluorescence in situ hybridization in parallel with immunohistochemistry (IHC) (IHC scores of 0‐1+, 2+, and 3+). Amplification was defined as HER2 / CEP17 ≥ 2. HER3 expression by IHC was analyzed in randomly selected cases (n = 224). IHC and fluorescence in situ hybridization results were compared using least squares linear regression. RESULTS: Overall, 17% of the EACs (116 of 673 EACs) were HER2 ‐amplified with an amplification frequency that was highest among IHC3+ cases (89%) and declined among IHC2+ cases (13%) and IHC0 to IHC1+ cases (4%). Among HER2 ‐amplified cases, the level of amplification increased linearly with HER2 membranous expression ( HER2 / CEP17 ratio: 7.9 in IHC3+ and 5.5 in IHC2+ vs 2.8 in IHC0 to IHC1+ [ P < .0001]), with 14% of amplified tumors demonstrating absent/faint expression (IHC0 to IHC1+). Polysomy 17 was not found to be associated with HER2 expression. Cytoplasmic HER3 expression was detected in 87% of tumors (195 of 224 tumors) and was found to be significantly associated with better differentiation ( P < .0001). Stepwise increases in HER3 expression were associated with higher HER2 expression levels ( P = .0019). CONCLUSIONS: Levels of HER2 protein expression and amplification were found to be linearly associated and highly concordant. Among amplified tumors with absent/faint expression, the level of amplification was low. Frequent expression of HER3 suggests its relevance as a therapeutic target, and its significant association with HER2 supports ongoing efforts to inhibit HER2/HER3 in patients with EAC. Cancer 2014;120:415–424 . © 2013 American Cancer Society . Abstract : Human epidermal growth factor receptor 2 (HER2) protein expression and gene amplification were found to be highly concordant in a large cohort of patients with esophageal adenocarcinoma, and human epidermal growth factor receptor 3 (HER3), an important interacting partner of HER2, was frequently expressed and demonstrated a stepwise positive association with HER2 expression. These findings may improve the selection of patients for HER2‐targeted therapy and support efforts to therapeutically target the HER2‐HER3 interaction.